Analysis and Visualization of Fuel Consumption Against Co2 Emission (Global Journal of Science Frontier Research, 2023)
CO2 emission has an adverse effect on the environment and cause greenhouse effect with significant negative climatic changes This subsequently lead global warming which hurts both human and crops It is important for us to perform visual analysis with available dataset using Canada as a case study